Design of a hybrid controller for solar and ocean wave energy harvester / \c Ahmad Shukri bin Fazil Rahman. - Ahmad Shukri Fazil Rahman (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2017)
The primary objective of this thesis is to present a hybrid controller that will tackle the control design and analysis problem of the study system. Based on the proposed approach, a hybrid control scheme for the wave energy conversion and PV has been presented. The hybrid controller will operate the harvester in an off-grid mode, with operating conditions as described in section 1.6. The hybrid controller for the study system will use sensor information to navigate its operation along pre-specified transition routes in response to differentsystem events. The following tasks have been established to accomplish the stated objective ; to develop the two system harvester modules, PV and Wave Energy Turbine (WET) for hybrid power system ; to propose control schemes based on the conventional control techniques for thetwosystemsharvester modules, i.e. the PVand wave energy unit ; to incorporate and configure the control schemes for the two system harvester modules, PVand WET.